Fish debris in sediments from the last 25 kyr in the Humboldt Current reveal the role of productivity and oxygen on small pelagic fishes - Salvatteci, R (2019)
RS is grateful to the Alexander von Humboldt foundation for granting a postdoctoral fellowship. We acknowledge the Institute del Mar del Peru (IMARPE) and the joint IMARPE-IRD projects PALEOTRACES and DISCOH for the support of this research. We also acknowledge the program CIENCIACTIVA that granted the research of climate change impacts on the upwelling ecosystem in the frame of the Master's Program in Marine Sciences at the Universidad Peruana Cayetano Heredia. This study was supported by the German Research Foundation through Sonderforschungsbereich 754 ("ClimateBiogeochemistry Interactions in the Tropical Ocean"). SEM observations were performed at the ALYSES facility (IRD, Sorbonne University, supported by grants from Region Ile-de-France). We deeply thank Bo Thamdrup, chief scientist of the Galathea-3 expedition (Leg 14), and Bente Lomstein, who conducted the core sampling onboard the RV Vaedderen. This paper is dedicated to the memory of Luc Ortlieb and Vicente Ferreira-Bartrina, great scholars, and friends.